2021
DOI: 10.1037/ser0000369
|View full text |Cite
|
Sign up to set email alerts
|

Borderline personality disorder and self-directed violence in a sample of suicidal army soldiers.

Abstract: There has been a sharp increase in the military suicide rates in 2004. While, borderline personality disorder (BPD) has a stronger association with suicide attempts than any other mental health disorder, there is limited evidence concerning the prevalence and scope of BPD symptoms among military personnel. This secondary data analysis compared active duty suicidal soldiers to characterize the presence-absence of BPD diagnostic criteria and lifetime history of self-directed violence in a suicidal military sampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 63 publications
1
4
0
Order By: Relevance
“…Of the four clusters of PD diagnoses, Cluster A had the lowest percentage of documented suicide attempts (2.9%). These findings mirror previous work that has found that individuals in Cluster B (especially those with BPD) have high rates of self-harm and suicide attempts (Fruhbauerova et al, 2021).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Of the four clusters of PD diagnoses, Cluster A had the lowest percentage of documented suicide attempts (2.9%). These findings mirror previous work that has found that individuals in Cluster B (especially those with BPD) have high rates of self-harm and suicide attempts (Fruhbauerova et al, 2021).…”
Section: Discussionsupporting
confidence: 90%
“…An evaluation of 955 service members admitted to Walter Reed for suicidal ideation or recent suicide attempt found that the most prevalent diagnoses were PD-NOS and BPD (George et al, 2019). Another study looking at active service members with suicidal ideation found that those with BPD had a higher number of incidents of self-injury and suicide attempts than those without BPD (Fruhbauerova et al, 2021). Both studies found high rates of specific PD diagnoses (BPD and PD-NOS) within military samples with suicidal ideation, indicating there may be incremental benefits of looking at specific subgroups of individuals with PD diagnoses, in addition to PDs overall, when assessing suicide risk.…”
mentioning
confidence: 99%
“…Clearly, clinical findings have already demonstrated the disturbing association between mental illness with more frequent NSSI, SI, and SA among civilian (Zetterqvist et al, 2013) and military samples (Fruhbauerova et al, 2019). Nevertheless, the results of our study, which was conducted among a typical, nonclinical young population of soldiers, suggest that the danger of self‐destructive behaviors hovers not only in clinical populations but also in normative populations.…”
Section: Discussionmentioning
confidence: 99%
“…One study estimated that 72.6% of BPD patients had a history of at least one suicide attempt in their lifetime [Soloff, 1994]. Fruhbauerova et al organized research to estimate the prevalence of BPD features in army personnel involved in suicidal behaviors [Fruhbauerova, 2019]. Around 27.7% of suicidal army soldiers fulfilled the criteria of BPD.…”
Section: Bpd and Self-harmmentioning
confidence: 99%
“…Around 27.7% of suicidal army soldiers fulfilled the criteria of BPD. The study also examined that BPD-diagnosed soldiers were younger and most likely unmarried than those without BPD features [Fruhbauerova, 2019]. Non-suicidal self-injury (NSSI) involves any intended direct damage or changes in the body's tissues without a conscious plan to commit suicide [Favazza, 1998].…”
Section: Bpd and Self-harmmentioning
confidence: 99%